Sarawak state election 2011: survey of voters' behaviour in BN critical areas of N9 Padungan, N10 Pending, N24 Beting Maro, N26 Bukit Begunan, N28 Engkelili and N30 Saribas / Chai Shin Yi... [et al.] - Chai, Shin Yi; Abang Spawi, Abang Yusuf; Jugah, Ivy (Universiti Teknologi Mara Cawangan Sarawak, 2012)
Sarawak held its ninth state election on May 20, 2006. Even though the Barisan Nasional won 62 out of the 71 seats, it was considered a major loss when compared with the victory of previous 2001 state election when the BN won 60 out of the 62 seats. Several factors have been accredited to the reasons behind BN's significant drop in electoral seats; land lease, increase of living standards, increase of oil prices, etc. The 2006 elections also made a rather significant impact on the 2008 Federal elections in particularly the Chinese voters. Several states in Peninsular Malaysia i.e Penang, Perak, Kedah and Selangor previously known to be BN's strongholds were lost to the opposition. Even though BN managed to retain its majority in Sarawak, the one seat won (Kuching) and maintained by opposition received a substantial increase of four-fold in votes from the 2001 state election. This figure signify a clear message to the BN that voters were serious about making a change and that they were willing to take a risk with the opposition in order to get more attention from the BN component party. With the upcoming General election, which is rumoured to be held simultaneously with Sarawak's state election (at the latest by April 21st if it were to occur), BN Sarawak in particular SUPP will be facing its most challenging election. In view of that, this research will seek to examine Sarawak voters' behaviour in BN critical areas of N9 Padungan, N10 Pending, N24 Beting Maro, N26 Bukit Begunan, N28 Engkelili and N30 Saribas